2007
DOI: 10.1086/511326
|View full text |Cite
|
Sign up to set email alerts
|

Herbig Ae/Be Stars in the Magellanic Bridge

Abstract: We have found Herbig Ae/Be star candidates in the western region of the Magellanic Bridge. Using the near infrared camera SIRIUS and the 1.4 m telescope IRSF, we surveyed about 3.0 deg x 1.3 deg (24 deg < RA < 36 deg, -75 deg < Dec. < -73.7 deg) in the J, H, and Ks bands. On the basis of colors and magnitudes, about 200 Herbig Ae/Be star candidates are selected. Considering the contaminations by miscellaneous sources such as foreground stars and early-type dwarfs in the Magellanic Bridge, we estimate that abou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…Finally, there are others types of young objects, such as Herbig–Haro stars (e.g. Subramaniam et al 2006; Nishiyama et al 2007), but we do not attempt to identify these specifically in this work.…”
Section: Analysesmentioning
confidence: 99%
“…Finally, there are others types of young objects, such as Herbig–Haro stars (e.g. Subramaniam et al 2006; Nishiyama et al 2007), but we do not attempt to identify these specifically in this work.…”
Section: Analysesmentioning
confidence: 99%
“…Muller et al (2004) reported that the MB is composed of two kinematically and morphologically distinct structures and shows a remarkable velocity offset around δ = −73.5 • in the δ-V rad plane. The discovery of molecular clouds (Mizuno et al 2006) and the possible detection of pre-mainsequence stars (Nishiyama et al 2007) in the MB strongly suggest that star formation in the MB is currently ongoing and possibly triggered by the last LMC-SMC interaction. Harris (2007) did not detect an older stellar population in the MB and thus suggested that the MB originates purely from gaseous components of the MCs.…”
Section: On the Possible Absence Of Older Stars In The Mbmentioning
confidence: 99%
“…What is the fate of the MCs and will they merge with the MW? Will the Bridge evolve into a dwarf galaxy (Nishiyama et al 2007)? Does the LMC have an ordinary bar and how does it influence the LMC evolution?…”
Section: Introductionmentioning
confidence: 99%